The impact of capital gains manipulation on the financial reporting of football clubs – the Plusvalenza case and Juventus - Házi, Bálint; Tóth, Balázs (Public Finance Quarterly, 2024)
In recent decades, football has attracted huge numbers of spectators and has become an increasingly popular sport among sports fans, a major entertainment industry and a growing concern for its financial sustainability. When assessing financial stability, it is essential to ensure that the financial statements are adequate, reliable and present a true and fair view. Playing rights are considered to be an indispensable resource for football clubs, but their evaluation is highly subjective. This also undermines the reliability of reporting and provides scope for manipulation of capital gains. This latter phenomenon has been evident in the operation of European football clubs, the most notable of which is Juventus. In this paper, we will attempt to examine the case of Juventus through a case study analysis, highlighting how the pricing of playing rights can help to portray a club’s wealth, income and financial situation in a more favourable light, and the short and long-term consequences of manipulation.